Pengaruh penggunaan blower pada kolektor surya sebagai alat alternatif untuk meningkatkan kualitas hasil pengeringan biji kopi di daerah Aceh - Andi Mulkan; Teuku Zulfadli (Jurnal POLIMESIN, 2021)
Naturally drying in the sun takes a very long time and product hygiene is also an obstacle because usually drying is done on open land. Using natural heat transfer, the time required for the coffee bean drying process ranges from 12-20 hours. The study describes a solar collector as an alternative device for drying in resulting coffee bean products with more hygienic without being exposed to dirt or bacteria. Shorter processes in which the quality of coffee beans increased were expected. The method used in this research is to analyze the heat absorption ability of the absorber using aluminium material which has been previously painted and the use of an air blower. The temperature inside was taken at thirty-minute intervals. Measurement of the mass of coffee beans was measured every 1-hour using digital scales. Similarly, mass and moisture content were also measured every 1 hour. From the results, it shows that the use of a blower with an airflow rate of 3.65 m/s with an average temperature of 56 ℃ can reduce the moisture content by 25.5%. For an air velocity of 4.55 m/s with an average temperature of 54.2 ℃, the moisture content reduces as much as 24.52%. Furthermore, for an airflow rate of 4.95 m/s with an average temperature of 52.7 ℃, the moisture decreased by 21.78% within 4 hours